Ecotoxicological evaluation of gilthead seabream (Sparus aurata) exposed to the antibiotic oxytetracycline using a multibiomarker approach. (October 2018) - Rodrigues, S.; Antunes, S.C.; Correia, A.T.; Nunes, B.
Abstract: Oxytetracycline (OTC) is an antibiotic widely used in human and veterinary medicines. Since the primary toxicity occurs mainly at molecular/biochemical levels, the study of different biological responses corresponds to a sensitive and crucial approach. The aim of the present study was to assess the toxic effects of OTC in gilthead seabream ( Sparus aurata ) through the use of multibiomarkers and elucidate about the possible toxicological mechanisms involved. S. aurata were acutely (96 h: 0.04–400 μg/L) and chronically (28 days: 0.0004–4 μg/L) exposed to OTC. Detoxification, antioxidant defense, lipid peroxidation, genotoxicity, neurotransmission and energy metabolism biomarkers were evaluated. OTC impaired the detoxification pathways and caused peroxidative damage and genotoxicity. The relevance of the here-obtained data is high, since significant effects were recorded for levels already reported to occur in the wild, meaning that environmentally-exposed marine organisms (including those cultured at fish farms) are not completely exempt of risks posed by OTC. Highlights: OTC can cause undesirable effects in exposed organisms (target and non-target). OTC impaired the detoxification pathways, and caused peroxidative damage and genotoxicity. Antioxidant responses, energetic imbalance and neurotoxicity were not observed. Marine organisms are not completely exempt of risks posed by OTC.